Polymeric nanoparticles containing kojic acid induce structural alterations and apoptosis-like death in Leishmania (Leishmania) amazonensis - Poliana Queiroz-Souza; Adan Galue-Parra; Lienne Silveira Moraes; Caroline Gomes Macedo; Ana Paula Drummond Rodrigues; Victor H. S. Marinho; Fabricio H. Holanda; Irlon M. Ferreira; Edilene Oliveira da Silva; Edilene Oliveira da Silva (Frontiers Media S.A., 2024)
Leishmaniasis encompasses a cluster of neglected tropical diseases triggered by kinetoplastid phatogens belonging to the genus Leishmania. Current therapeutic approaches are toxic, expensive, and require long-term treatment. Nanoparticles are emerging as a new alternative for the treatment of neglected tropical diseases. Silk Fibroin is a biocompatible and amphiphilic protein that can be used for formulating nanoemulsions, while kojic acid is a secondary metabolite with antileishmanial actions. Thus, this study evaluated the efficacy of a nanoemulsion, formulated with silk fibroin as the surfactant and containing kojic acid (NanoFKA), against promastigote and amastigote forms of Leishmania (Leishmania) amazonensis. The NanoFKA had an average particle size of 176 nm, Polydispersity Index (PDI) of 0.370, and a Zeta Potential of −32.3 mV. It presented inhibitory concentration (IC50) values of >56 μg/mL and >7 μg/mL for the promastigote and amastigote forms, respectively. Ultrastructural analysis, cell cycle distribution and phosphatidylserine exposure showed that NanoFKA treatment induces apoptosis-like cell death and cell cycle arrest in L. (L.) amazonensis. In addition, NanoFKA exhibited no cytotoxicity against macrophages. Given these results, NanoFKA present leishmanicidal activity against L. (L.) amazonensis.